Presence of renin within intramitochondrial dense bodies of the rat adrenal cortex - Peters, Jörg; Kränzlin, Bettina; Schaeffer, S.; Zimmer, Jörg; Resch, S.; Bachmann, Sebastian; Gretz, Norbert; Hackenthal, Eberhard (American journal of physiology. Endocrinology and metabolism, 1996)
It has been suggested that tissue-specific expression of the genes of the renin-angiotensin system (RAS) leads to local generation of angiotensin (ANG) II with specific physiological implications. We demonstrate here that an intracellular RAS exists in adrenal glomerulosa cells; 60 h after bilateral nephrectomy and hemodialysis, renin and prorenin were eliminated from the circulation, whereas intra-adrenal renin content increased (control rats: 2 +/- 0.5 ng ANG I.mg-1.h-1; anephric rats: 25 +/- 2). Thus renin is produced locally within adrenal cells. We obtained immunocytochemical and biochemical evidence for the presence of renin within intramitochondrial dense bodies of the zona glomerulosa. After nephrectomy, dense bodies increased in number, size, and renin content (control rats: 2.5 +/- 0.7 ngANGI.mg-1.h-1; anephric rats: 43 +/- 7). Angiotensin-converting enzyme (ACE) was also present within mitochondria and their dense bodies. In addition, in adrenal cortex of anephric rats, giant dense bodies were observed, which contain renin and strongly react with an anti-angiotensinogen antibody. The localization of renin, ACE, and angiotensinogen at these sites provides new evidence for the existence of an intracellular adrenal RAS.
Gesehen am 05.06.2025